Analisis Normatif Tanggung Jawab Pemerintah Daerah dalam Pemenuhan Hak Kesehatan dan Keselamatan Nelayan Tradisional di Kabupaten Bangka Barat - Bunga Permatasari; Aditya Pamungkas; Salmi; Ave Agave Christina Situmorang (PROGRESIF: Jurnal Hukum, 2024)
This study aims to analyze the normative responsibilities of the West Bangka Regency Government in fulfilling the health and safety rights of traditional fishermen. As a maritime entity, the fishing profession in this region carries high risks that are often overlooked due to regulatory complexity and economic interests. The research method used is a normative method with a legislative approach and the theory of state responsibility. The results of the discussion indicate that despite the mandate through Law No. 7 of 2016 and the free BPJS program, there are still regulatory gaps related to Occupational Safety and Health standards and protection for informal workers. Implementation in the field is still hampered by limited maritime medical infrastructure at coastal health centers and a lack of supervision of safety standards on traditional vessels. In conclusion, the West Bangka Regency Government needs to immediately codify the protection of fishermen into an inclusive Regional Regulation, strengthen the community-based social security system, and increase maritime medical capacity to guarantee the constitutional rights of fishermen in a sustainable manner.